Optical properties and structure of jc-1 j-aggregates in solutions - Sorokin, A. V. (Biophysical Bulletin, 2008)
Using the stationary optical spectroscopy the optical properties of J-aggregates of cyanine dye JC-1 have been investigated. The model of the J-aggregates structure has been proposed. It has been supposed that at high dye concentration the dye dimers are the main building unit of the J-aggregates linear chains. It has been shown the absorption and luminescence spectra of the dimers. Such model of JC-1 J-aggregates structure is proposed for the first time